Prospek Pendidikan Bahasa Arab di Indonesia pada Era Perkembangan Zaman - Hanani, Nurul (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2016)
This time educators of Arabic language seem to just consider Arabic language asa tool (wasilah) to understand Islamic texts, and not yet making it as a separatediscipline that needs to be developed through a variety of research. Challenges andissues in Arabic education cannot be solved personally, but through institutionalapproach and involve many parties. Arabic language is an opportunity thatprovides brighter and more propmising prospect in the future. Epistemologyof science and the curriculum needs to be addressed and oriented towards theestablishment of competitive ability in this global era. These all require manyparties to work together in a unifying vision, mission, policy and developmentthat is based on academic studies.